Immune responses against Helicobacter pylori-specific antigens differentiate relapsing remitting from secondary progressive multiple sclerosis - Efthymiou, Georgios (Sci Rep, 2017)
To assess whether Helicobacter pylori (Hp) antibody (ab) reactivity against individual Hp antigens is pathogenetically relevant to multiple sclerosis (MS), we systematically investigated prevalence and clinical significance of abs against 14 immunodominant and subdominant Hp antigens by ELISA and immunoblotting in 139 consecutive MS patients with relapsing-remitting (RRMS, n = 102) or secondary progressive (SPMS, n = 37). Sera from 39 patients with Parkinson’s disease (PD), 21 with Alzheimer’s disease (ALZ) and 68 healthy controls (HCs), were also tested. Anti-flagellin (18.3%) and anti-p41 (25.0%) abs in MS were less frequent than in HCs (39.4%, 48.5%, respectively). Abs against 5 of the 14 antigens were less frequent in RRMS than HCs, including p41, p54-flagellin, p29-UreA, p67-FSH, and p120-CagA. Anti-VacA abs were more frequent in SPMS than in HCs (42.1 vs 12.1%, p = 0.019). Anti-p54, anti-p29-UreA and anti-p26 correlated with extended disability status scale (EDSS) (p = 0.017, p = 0.005, p = 0.002, respectively). Anti-p26 and anti-p17 correlated with the number of relapses (p = 0.037 and p = 0.047, respectively). This is the first comprehensive analysis of ab reactivities against most Hp antigens in MS patients. Ab responses differ between MS and HCs and between RRMS and SPMS, being more prevalent in SPMS than RRMS, thus suggesting an association between anti-Hp and the former type of MS.